The Effect of Bank Liquidity and Efficiency on Non-Interest Income with National Income as Variables Moderator - Dadang Agus Suryanto; Disman Disman; Nugraha Nugraha; Ika Putera Waspada; Sugiyanto Sugiyanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Empirically, non-interest income from banks in Indonesia has increased in the last five years. Apart from being caused by efficiency issues and the level of risk in interest income, the increase in non-interest income was due to the proliferation of electronic-based banking services. In an effort to understand the influence factors on non-interest income, this study examines the effect of market concentration on third party funds, credit market concentration, capital adequacy, bank liquidity, bank efficiency, non-performing loans, leverage, and reference interest rates on non-interest income. In addition, testing the effect of bank and macroeconomic characteristics variables on non-interest income with national income as a moderating variable and the effect of bank and macroeconomic characteristics on non-interest income with inflation as a moderating variable. This research uses descriptive methods and causality. The research was conducted at conventional National Commercial Banks in Indonesia, which is divided into the periodization of the financial crisis era, namely 2006-2011 and post-financial crisis, namely 2012-2017. The data collection technique used by researchers is the documentation method. The data analysis technique was performed using unbalance panel data regression analysis. The results showed that bank liquidity and bank efficiency had a significant effect.